A method to measure redox potential (Eh) and pH in agar media and plants shows that fungal growth is affected by and affects pH and Eh - Bousseta, L.; Ermela. M.; Soglonou, B.; Husson, O. (Elsevier, 2019)
The specificities of the plant environment and its effects on fungal growth are not yet fully explored. Both pH and Eh play a key role during this interaction, but are often studied independently or at different scales. We aimed at investigating whether the methods developed for the joint characterization of the pH and Eh in soil could be transposed to fungi. On artificial media, the growth of all 16 species tested significantly altered either Eh, pH or both. Measuring Eh reveals that even the species not modifying pH can have an impact on the surrounding environment. Reciprocally, fungi responded to pH and Eh parameters, both quantitatively with a decrease in colony diameter and qualitatively with colony aspect repeatedly and thoroughly modified. In infected oilseed rape plant stems, pH and Eh were significantly altered. The observed alcalinisation or acidification correlates with canker length. The joint characterization of both parameters will allow understanding the impact of fungi on their environment, and conversely of the environment on fungal growth. The availability of methods for measurement opens the prospect to study combinations of stresses, and get an understanding of the involvement of pH and Eh modifications in these interactions.